2012
DOI: 10.4103/0970-9371.93218
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of ovarian tumors with histological correlation

Abstract: Background:Till today, there has been some hesitation to accept the role of fine needle aspiration cytology (FNAC) in pelvic mass. We have tried to study the role of ultrasonography (USG) and computed tomography (CT) guided FNAC as diagnostic and supportive investigation for ovarian tumors.Aim:To evaluate the current status of image-directed percutaneous aspiration of ovarian neoplasm for the purpose of early detection of malignancy.Materials and Methods:Seventy-four fine needle aspirations of ovarian neoplasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 17 publications
4
12
0
Order By: Relevance
“…Malignant tumours were found in all age groups, with a predominance in the elderly, supporting the findings of Mehdi et al [1] and Khan et al [2]. We found a higher number of malignant cases (40 cases, 57.14%), in agreement with the results of Bandyopadhyay et al [11]. However, Khan et al [2 ]and Goel et al [10] found a larger percentage of benign and non-neoplastic cases in their series.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Malignant tumours were found in all age groups, with a predominance in the elderly, supporting the findings of Mehdi et al [1] and Khan et al [2]. We found a higher number of malignant cases (40 cases, 57.14%), in agreement with the results of Bandyopadhyay et al [11]. However, Khan et al [2 ]and Goel et al [10] found a larger percentage of benign and non-neoplastic cases in their series.…”
Section: Discussionsupporting
confidence: 83%
“…It is always difficult to differentiate borderline surface epithelial tumours from well-differentiated carcinomas, because hypercellularity and anaplasia are the features of both entities. Similar-type discrepancies have also been reported by many other authors [3,10,11,21]. …”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations